Religious painting in the work of Salvatore Tonci - Yurovetskaya, Anastasiya V. (Actual Problems of Theory and History of Art, 2012)
The article is dedicated to works of art on Christian themes created by the artist Salvatore Tonci in graphic and oil painting technique. Complex approach to this aspect of his works made it possible to take a fresh look at cultural heritage of a master, whose name is in the first place connected with the portraiture at the turn of the 18th and 19th century.
Keywords: Salvatore Tonci; Christian themes in art; oil-painting; graphic works; the Vladimir and Suzdal Museum